Planning of consumption and buyer behaviour in households 1976-1977 - Face-to-face interview - Haglund, Lars (University of Gothenburg, 1982)
The study was designed with a two-stage research approach. The first stage included a large sample, mail survey with about 1 200 households participating. The second stage consisted of personal interviews with a sub-sample of respondents from the mail survey. About 130 households were interviewed in this second survey. The purpose with the study is to describe the various planning activities that a household goes through when buying goods and services from a market system; to analyse the relationship between the situation and the characteristics of the household and the planning behaviour; to evaluate the efficiency of planning, i.e. to study the effect of different planning on the buyer behavior and the satisfaction in the household.

The study was designed with a two-stage research approach. The first stage included a large sample, mail survey with about 1 200 households participating. The second stage consisted of personal interviews with a sub-sample of respondents from the mail survey. About 130 households were interviewed in this second survey. The purpose with the study is to describe the various planning activities that a household goes through when buying goods and services from a market system; to analyse the relationship between the situation and the characteristics of the household and the planning behaviour; to evaluate the efficiency of planning, i.e. to study the effect of different planning on the buyer behavior and the satisfaction in the household.
Konsumtions- och köpplanering i hushåll 1976-1977 - Intervjuundersökningen
Keywords: consumption; konsumtion; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Social Sciences; Samhällsvetenskap; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap